A Specific Inhibitor of Polypeptide-Chain Initiation in Escherichia coli - Lee-Huang, Sylvia (1973)
An inhibitor of polypeptide-chain initiation was isolated from E. coli cells. This protein inhibits formation of the 30S or 70S initiation complex with either fMet-tRNA(f) as initiator and AUG, MS2 RNA, or late T4 RNA as messenger, or acPhe-tRNA as initiator and poly(U) as messenger. Chain elongation, e.g., poly(U) translation at high Mg(2+) concentration, is not inhibited. The inhibitor is rendered ineffective when active aminoacylation of tRNA is taking place, e.g., during natural mRNA translation. This inhibitor is distinct from the so-called interference (i) factors, which interfere exclusively with the action of initiation factor 3. Since the new inhibitor can apparently be turned on and off, it may have a regulatory function in translation.